2013
DOI: 10.1590/s0100-736x2013000300012
|View full text |Cite
|
Sign up to set email alerts
|

Sistemas produtivos de caprinocultura leiteira no semiárido paraibano: caracterização, principais limitantes e avaliação de estratégias de intervenção

Abstract: Oito propriedades de leite caprino do semiárido paraibano foram acompanhadas, multidisciplinarmente, durante dois anos, com os objetivos de identificar os principais fatores limitantes da produção, assim como propor e avaliar estratégias de intervenção. Utilizou-se um questionário para obtenção de informações sobre as propriedades e práticas de manejo. Avaliou-se o balanço forrageiro de cada propriedade e foram feitas propostas para correção. Os animais foram identificados para que se viabilizasse a escrituraç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 10 publications
1
11
0
7
Order By: Relevance
“…Além da determinação anual do perfil de resistência dos parasitas aos anti-helmínticos, uma medida que contribui para mitigar o problema de resistência é a utilização de tratamentos seletivos, que consiste em tratar parte do rebanho, que pode ser determinado por determinação da quantidade de ovos por grama de fezes (OPG) ou por outros critérios: idade, grau de anemia (FAMACHA), estado corporal, edema submandibular, aspectos das fezes, condições de pelame , Riet-Correa et al 2013 Na pastagem, as larvas eclodem dos ovos e atingem a forma de L3 (3º estágio larval, responsável pela infecção no hospedeiro) em 4-7 dias. Em climas temperados as larvas podem sobreviver por até 18 meses (O'Connor et al 2006.…”
Section: Introductionunclassified
“…Além da determinação anual do perfil de resistência dos parasitas aos anti-helmínticos, uma medida que contribui para mitigar o problema de resistência é a utilização de tratamentos seletivos, que consiste em tratar parte do rebanho, que pode ser determinado por determinação da quantidade de ovos por grama de fezes (OPG) ou por outros critérios: idade, grau de anemia (FAMACHA), estado corporal, edema submandibular, aspectos das fezes, condições de pelame , Riet-Correa et al 2013 Na pastagem, as larvas eclodem dos ovos e atingem a forma de L3 (3º estágio larval, responsável pela infecção no hospedeiro) em 4-7 dias. Em climas temperados as larvas podem sobreviver por até 18 meses (O'Connor et al 2006.…”
Section: Introductionunclassified
“…Although silage and haymaking constitute good forage conservation technique options, properties in the Brazilian NE are not concerned at this level; only RN (50 %) and SE (42.3 %) employed silage to feed the herd. The lack of knowledge about the techniques, the cost of extrafamiliar labor in the different phases of production, and the competition with the production of food for human consumption has justified the disuse of these techniques and the lack of tradition in the storage and conservation of forage by part of the producers (RIET-CORREA et al, 2013). In this context, even with the increasing need for techniques that guarantee the farming productivity throughout drought periods in the Brazilian NE region, misinformation and technical limitations have influenced this choice.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite the great concentration of herds, high productive potential, and the sociocultural aspects related to goat husbandry in the NE, research has shown a very limited productive profile for goat farming. These conditions arise from the peculiar circumstances of this chain, including cultural (rusticity of farms), conjectural (prices and markets), and ecological aspects (climate) (RIET-CORREA et al, 2013;SILVA et al, 2013), which limit the development of regional goat farming.…”
Section: Introductionmentioning
confidence: 99%
“…Riet- Correa et al (2013) analyzed dairy goat breeding in the semiarid region of Brazil, reporting that farmers had been experiencing problems to maintain production during the dry seasons. Success in these conditions depended largely on the government's assistance policies.…”
Section: Resultsmentioning
confidence: 99%